An Assessment of the influence of technological collaboration on competitiveness of small to medium enterprises: a case of Speroni Irrigation - Marekera, Tendayi (BUSE, 2023)
This study explores the significant influence of technological collaboration on the competitiveness of irrigation Small and Medium Enterprises (SMEs) in Zimbabwe, with a specific focus on Speroni Irrigation Pvt Ltd, an established irrigation SME that supplies equipment and services to farmers. The primary objective of this research is to achieve a comprehensive understanding of the impact of technological collaboration on Speroni Irrigation's competitiveness and to propose a model for enhancing collaboration among SMEs in the irrigation sector. The study aims to accomplish four key objectives: Firstly, it seeks to assess the current state of technological collaboration within Speroni Irrigation, encompassing an examination of the types of collaboration, sources of collaboration, and resultant outcomes. Secondly, it investigates the influence of technological collaboration on the competitiveness of Speroni Irrigation, specifically in terms of factors such as innovation, quality, customer satisfaction, and market share. Thirdly, the study aims to identify and analyse the factors that hinder collaboration efforts within the organization, including resource limitations, issues related to trust-building, incentives, and coordination challenges. Lastly, based on an extensive literature review and empirical findings, the research endeavours to design a model for technological collaboration that can effectively enhance the competitiveness of SMEs in the irrigation sector. To achieve a comprehensive understanding, the study employs a mixed methods approach, combining qualitative and quantitative data collection techniques. Interviews, questionnaires, and document analysis are utilized to gather relevant data. Thematic and content analysis, in conjunction with descriptive statistics, are employed to analyse the collected data, allowing for a rich and nuanced interpretation of the findings. The research findings indicate that technological collaboration has a positive impact on various aspects of Speroni Irrigation's competitiveness, including innovation, quality, customer satisfaction, and market share. However, the study also reveals the presence of challenges that hinder effective collaboration efforts. These challenges primarily revolve around resource limitations, trust-building processes, incentives for collaboration, and coordination issues. Considering the research findings, the study provides practical recommendations to overcome these barriers and enhance the benefits of technological collaboration for Speroni Irrigation and other irrigation SMEs in Zimbabwe. Furthermore, the research proposes a model that can serve as a framework for fostering and enhancing technological collaboration among SMEs in the irrigation sector. By implementing the recommendations and adopting the proposed model, irrigation SMEs in Zimbabwe can strengthen their competitiveness and improve their overall performance.
Keywords: Technological collaboration; Small to Medium Enterprises (SMEs); Competitiveness; Speroni Irrigation